Stunning effects in radioiodine therapy of thyroid carcinoma - Koch, W.; Knesewitsch, P.; Tatsch, K.; Hahn, K. (Nuklearmedizin - NuclearMedicine, 2003)
In radioiodine therapy for malignant thyroid disease, the pre-therapeutically administered iodine-131-dose can reduce the potential of thyroid or thyroid carcinoma cells to absorb the following therapeutic iodine-131-dose, possibly leading to its failure. This so called stunning effect is controversially discussed in the scientific community. Here we summarize and evaluate publications with regard to the existence and the effects of stunning as well as possible countermeasures.
Keywords: Radioiodine therapy; stunning; iodine-123-scintigraphy